2022
DOI: 10.3390/insects13020133
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effect of the Dietary Protein to Carbohydrate Ratio on Personality in the Dubia Cockroach

Abstract: Animal personality, defined by behavioral variations among individuals consistent over contexts or time, is shaped by genetic and environmental factors. Among these factors, nutrition can play an important role. The Geometric Framework of Nutrition has promoted a better understanding of the role of the macronutrient proportion in animal development, survival, reproduction, and behavior, and can help to disentangle its modulatory effect on animal personality. In this study, we investigated the effects of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Once all arenas were in position and cameras focused, I started the recording and left the room. The lights automatically switched off after 40 min, and so, the trial began 40 min after I left the room, in darkness, which is when B. dubia is active (Bouchebti et al, 2022 ). I returned 2 h after leaving to end the trial, meaning the trials lasted 80 min.…”
Section: Methodsmentioning
confidence: 99%
“…Once all arenas were in position and cameras focused, I started the recording and left the room. The lights automatically switched off after 40 min, and so, the trial began 40 min after I left the room, in darkness, which is when B. dubia is active (Bouchebti et al, 2022 ). I returned 2 h after leaving to end the trial, meaning the trials lasted 80 min.…”
Section: Methodsmentioning
confidence: 99%
“…Once all arenas were in position and cameras focused, I started the recording and left the room. The lights automatically switched off after 40 minutes, and so the trial began 40 minutes after I left the room, in darkness, which is when B. dubia is active (Bouchebti et al ., 2022). I returned two hours after leaving to end the trial, meaning the trials lasted 80 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies using this approach have shown how the intake of nutritionally unbalanced diets influences a variety of physiological, behavioural and life‐history traits. For instance, an unbalanced protein to carbohydrate (P:C) ratio can affect the lifespan (Le Couteur et al, 2016; Lee et al, 2008), reproduction (Jensen et al, 2015; Solon‐Biet et al, 2015), immunity (Ponton et al, 2011) or even personality traits of individuals (Bouchebti, Cortés‐Fossati, et al, 2022; Han & Dingemanse, 2017).…”
Section: Introductionmentioning
confidence: 99%